Expression patterns of some development-essential genes and growth-related imprinted genes throughout preimplantation stages of embryos fertilized and developed in vivo and in vitro - Ramos, Gliceria B.
It is claimed widely that culture conditions, specifically the addition of serum or serum albumin, could alter the expressions of development-essential genes and growth-related imprinted genes, thus, responsible for the deviations in the phenotypic characteristics in assisted reproductive technology (ART)-mediated offspring. However, most investigations employ serum at either suboptimal or supraoptimal concentrations, assessed gene expressions mostly at the blastocyst stage of development and lack comparison of gene expression patterns of in vitro fertilized and developed embryos with those of in vivo fertilized and developed embryos in animal models. Hence, this study determined and compared the relative expression and chronological expression patterns of some development-essential genes, DNMT1, Nanog, Fgf4, and EzH2, and the highly susceptible growth-related imprinted genes, H19, Igf2, Grb10 and Mest, of in vivo-and in vitro-fertilized and developed embryos at each stage of preimplantation development. Standard culture conditions using Whittingham?s medium (WM), supplemented with 3mg/ml bovine serum albumin (BSA) and 100ug/ml EDTA, were employed and embryos derived from B6C3F1 and B6D2F1 females mated with ICR males were utilized. Gene expressions were analyzed by Quantitative Real Time Polymerase Chain Reaction (QRT-PCR). The relative expressions of the development-essential genes, DNMT1, Nanog, Fgf4, and EzH2, of in vivo-fertilized and developed embryos, basically exhibited undetectable to slightly detectable expressions during early cleavage stages. Noticeable expressions were exhibited mostly at blastocyst stage aside from the most evident expression at morula stage and at 2-cell stage for Nanog and Fgf4 respectively. The relative expressions of all four development essential genes of in vitro-embryos exhibited deviations from that of the in vivo-embryos. The incurred deviations, however, were not significantly different in all of the four genes. The relative expressions of the imprinted genes H19 and Igf2 of in vivo embryos from both B6C3F1 and B6D2F1 were identically undetectable throughout preimplantation development. In in vitro embryos, noticeable expression was detected only at blastocyst stage. Igf2 expression of in vitro embryos from B6C3F1 showed significantly higher than those of in vivo embryos. The relative expression of Grb10 of in vivo-embryos differed between B6C3F1 and B6D2F1 where the former exhibited declining expression pattern to undetectable expression at 8¬cell and blastocyst stages but with an evident expression at morula stage. The latter exhibited a most evident expression at 2-cell stage followed by a slightly detectable expression at 8-cell stage to undetectable expression at morula and blastocyst stages. In vitro-embryos showed noticeably higher expressions at 2-cell and 4-cell stages in B6C3F1 and B6D2F1, respectively, but these were not significantly different from those of the in vivo-embryos. A declining expression pattern of Mest of in vivo-embryos was closely similar between strains. Expression was low at PN stage, undetectable from 4-cell to morula stage and slightly detectable at blastocyst stage. Mest relative expressions of in vitro-embryos showed evident deviations from those of in vivo embryos but these were not significantly different. The chronological gene expressions of the in vitro-embryos likewise exhibited deviations from that of the in vivo-embryos. The results showed that in vitro fertilization and subsequent embryo culture under standard conditions, with optimized serum concentrations, did not significantly alter the relative gene expressions of the four development-essential genes and of the growth-related imprinted genes except for Igf2. The results may not be statistically significant as analyzed but these may still have biological significance. It is possible that these deviations of the in vitro embryos from those of in vivo embryos in the relative gene expressions and temporal gene expression patterns may cause disturbance in the subsequent postimplantation development. Further, due to the fact that Igf2 is essential to the pathogenesis of Beckwith-Wiedemann Syndrome, the results may warrant further caution on the use of assisted reproductive techniques.